2019
DOI: 10.1016/j.jdsr.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and periodontal microorganisms

Abstract: Summary Resolution of dysbiosis following treatment for periodontal disease and tobacco dependence has been reported in longitudinal intervention studies. In the present report, we evaluated the biological findings regarding the effect of smoking on the periodontal microbiome. A standardized electronic search was conducted using MEDLINE; overall, 1099 papers were extracted. Studies that addressed the relationship between tobacco and periodontal pathogens were included. Finally, 42 papers were deemed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 46 publications
2
42
2
4
Order By: Relevance
“…It is well established that smoking-associated periodontitis is not just a deliberation of poor oral hygiene but extends to provide an appropriate niche for colonization of bacteria such as P. gingivalis, Prevotella intermedia, and Actinobacillus actinomycetemcomitans, facilitating development of periodontal lesions (Eggert et al, 2001). It has been reported that exposure to nicotine modulated the immunological functions via P. gingivalis, promoting biofilm formation by interacting with commensal oral bacteria Streptococcus gordonii (Hanioka et al, 2019). Moreover, the salivary microbiome exemplifies bacteria from different surfaces in the oral cavity (Gao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that smoking-associated periodontitis is not just a deliberation of poor oral hygiene but extends to provide an appropriate niche for colonization of bacteria such as P. gingivalis, Prevotella intermedia, and Actinobacillus actinomycetemcomitans, facilitating development of periodontal lesions (Eggert et al, 2001). It has been reported that exposure to nicotine modulated the immunological functions via P. gingivalis, promoting biofilm formation by interacting with commensal oral bacteria Streptococcus gordonii (Hanioka et al, 2019). Moreover, the salivary microbiome exemplifies bacteria from different surfaces in the oral cavity (Gao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The predominance of these periodontal pathogens in the oral cavity of ES and combustible cigarette users is a reflection of severely compromised periodontal health (p = 0.001) as depicted in Table S1. It has been shown that nicotine and its metabolite cotinine, as well as treatment with a cigarette smoke extract, can alter the function of key periodontal pathogens such as P. gingivalis and promote biofilm formation, colonization, and infection (Hanioka et al, 2019). Granulicatella is a known commensal of the human oral microbiome, however, which has been implicated in endodontic infection (Siqueira and Rô ç as, 2006) and is linked to increased risk of systemic diseases, such as pancreatic cancer related to oral inflammation (Farrell et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that successful or temporary smoking cessation activates the periodontal healing response. A few studies have reported differences in the microbiome in subgingival plaque between smokers and nonsmokers [9]. Generally, SRP leads to intensive qualitative changes in bacterial flora, which explains the benefits of SRP in the three groups in this study, even among nonquitters.…”
Section: Discussionmentioning
confidence: 51%
“…In this study, smoking is a factor that will be assessed in relation to the treatment outcome as many studies have documented less significant improvements from smokers in response to nonsurgical therapy. [13,14] In addition, higher numbers of periodontal pathogens are associated with the smokers, [15] which negatively affect the host immune response, including impaired neutrophil function, lowered immunoglobulin production, and reduced fibroblast function. [14] Persisting deficiency of prognostic information in the management of periodontitis underscores the importance of the study aimed at determining the effectiveness of NSPT provided by GDP in training and to explore the correlation between prognostic indicators and treatment outcome.…”
Section: Introductionmentioning
confidence: 99%